2013
DOI: 10.1002/lt.23756
|View full text |Cite
|
Sign up to set email alerts
|

Improved renal function in liver transplant recipients treated for hepatitis C virus with a sustained virological response and mild chronic kidney disease

Abstract: Hepatitis C virus (HCV) is associated with renal complications. We aimed to determine whether a sustained virological response (SVR) was associated with improvements in renal function (RF) in liver transplant (LT) recipients treated for HCV. Changes in RF were compared 1, 3, and 5 years after therapy as a function of the stage of chronic kidney disease (CKD) before treatment (BT). Variables associated with renal dysfunction [RD; 4-variable Modification of Diet in Renal Disease (MDRD-4) value 60 mL/minute] at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In a study of HCV-infected liver transplant recipients, DAAs and SVR improved renal function in those with mild CKD. 21 A prior study including 57 patients with eGFR < 60 ml/min per 1.73 m 2 showed SVR was associated with improvement in eGFR in a multivariable model. 22 A recent prospective study of 94 patients with HCV treated with sofosbuvir showed an average improvement in eGFR of approximately 10 ml/min per 1.73 m 2 at 1 year; however, there were only 9 patients with CKD, defined as eGFR < 45 ml/min per 1.73 m 2 in this study.…”
Section: Discussionmentioning
confidence: 95%
“…In a study of HCV-infected liver transplant recipients, DAAs and SVR improved renal function in those with mild CKD. 21 A prior study including 57 patients with eGFR < 60 ml/min per 1.73 m 2 showed SVR was associated with improvement in eGFR in a multivariable model. 22 A recent prospective study of 94 patients with HCV treated with sofosbuvir showed an average improvement in eGFR of approximately 10 ml/min per 1.73 m 2 at 1 year; however, there were only 9 patients with CKD, defined as eGFR < 45 ml/min per 1.73 m 2 in this study.…”
Section: Discussionmentioning
confidence: 95%
“…(46,47) The improvements in renal function seen in this study folowing DAA therapy are likely to reflect resolution of immune complex disease and improvement in diabetic control. (38,48,49) Several measures were taken to minimize potential confounders of immunosuppression and ongoing metabolic treatment. All patients were on stable antirejection therapy and were steroid free for at least 3 months after liver transplant.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, current guidelines recommend to refer to a nephrologist in case of eGFR decline by > 25% or to a level < 60 ml/min [ 42 ]. Moreover, we cannot exclude that this slight decline could be followed by a late improvement, as previously found in liver transplant recipients with mild chronic kidney disease that achieved SVR after interferon-based regimens [ 43 ].…”
Section: Discussionmentioning
confidence: 92%